Dual pathways linking mindfulness to life satisfaction and depression: the mediating roles of self-compassion and rumination in Chinese university students - Yunpeng Wu; Liping Qin; Xizheng Xu; Yu Tian; Zhe Jia (BMC Psychology)
Abstract Objective Mindfulness has been consistently linked to mental health benefits; however, the underlying mechanisms relating mindfulness to life satisfaction and depression remain underexplored. This study develops and empirically examines the Dual Pathways Mindfulness Model (DPMM), which posits that mindfulness is associated with mental health through sequential mechanisms involving self-compassion and rumination among university students. Methods A cross-sectional survey involving 1,409 Chinese university students was conducted. Structural equation modeling (SEM) was used to test the hypothesized sequential mediation model. Indirect effects were examined using bias-corrected bootstrap confidence intervals. Results Mindfulness was positively associated with life satisfaction (Effect = 0.080, p < 0.01) and negatively associated with depression (Effect = −0.180, p < 0.001). Self-compassion significantly mediated both associations, linking mindfulness to higher life satisfaction (Indirect effect = 0.057, 95% CI [0.05, 0.07]) and lower depression (Indirect effect = -0.033, 95% CI [−0.04, −0.03]). Rumination also served as a significant mediator for life satisfaction (Indirect effect = 0.067, 95% CI [0.02, 0.04]) and depression (Indirect effect = −0.064, 95% CI [ −0.07, −0.05]). Furthermore, a sequential mediation pathway was identified: higher mindfulness was associated with greater self-compassion, which was linked to lower rumination, ultimately associated with increased life satisfaction (Indirect effect = 0.020, 95% CI [0.01, 0.03]) and decreased depressive symptoms (Indirect effect = -0.039, 95% CI [−0.05, −0.03]). Conclusion This study proposes and validates the DPMM, a novel model explaining how mindfulness relates to mental health through interconnected self-regulatory processes. By identifying self-compassion and rumination as sequential mediators, the findings offer theoretical insights into the psychological mechanisms linking mindfulness to enhanced well-being. While the cross-sectional design precludes causal claims, the results provide a foundational framework to guide future longitudinal studies and inform mental health promotion strategies grounded in mechanism-based understanding.